The wit & wisdom of Freddy and his friends - Brooks, Walter R., 1886-1958.; Wiese, Kurt, 1887-1974; Koslosky, Sarah (Woodstock, NY : Overlook Press, 2000)
A collection of quotations from the twenty-six books that Walter R. Brooks wrote about Freddy the Pig and his friends on and around Bean Farm.
Inventariado, 2025/VM
Keywords: Novela juvenil estadounidense